Potential Impact of the COVID-19 Pandemic on Sexual and Reproductive Health in Nepal - Puri, Mahesh Chandra; Stone, Lucy (Journal of Nepal Health Research Council, 2020)
The national lockdown imposed in Nepal as a response to the COVID-19 pandemic is having indirect consequences on sexual and reproductive (SRH) in Nepal. Although the Government of Nepal and partners have committed to ensuring the continuity of SRH services during the pandemic, this comment aims to illustrate the potential impacts to SRH if these commitments are not met. Keywords: COVID-19; Nepal; reproductive health; sexual health.